Pengembangan Media Pembelajaran Fisika pada Materi Tata Surya SMP/MTs Menggunakan Augmented Reality (AR) Berbasis Unity 3D - Firdaus, Oka; Idrus, Hadiyati; Chandra, Artha Nesa; Imamora, Marjoni (Edusainstika: Jurnal Pembelajaran MIPA, 2024)
The aim of this research is to develop Augmented Reality (AR) learning media for the Solar System tailored for SMP/MTs students, ensuring that it is valid, practical, and effective. This study employs a Research and Development (R&D) methodology, utilizing the 4-D development model, which consists of the stages: define, design, develop, and disseminate. However, due to time and cost constraints, this research was conducted only up to the development stage.The findings indicate that the Augmented Reality learning media developed is highly valid, achieving a validity score of 93.5%. In terms of practicality, the student response questionnaire results demonstrate that the media is very practical, with a score of 91.8%. These results suggest that the Augmented Reality Solar System learning media for SMP/MTs is suitable for use as an effective learning resource in schools at the SMP/MTs level